Neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios and prognosis after aneurysmal subarachnoid hemorrhage: a cohort study - Oliveira, Adilson Jose Manuel de; Rabelo, Nicollas Nunes; Telles, João Paulo Mota; Solla, Davi Jorge Fontoura; Coelho, Antonio Carlos Samaia da Silva; Barbosa, Guilherme Bitencourt; Barbato, Natália Camargo; Yoshikawa, Marcia Harumy; Teixeira, Manoel Jacobsen; Figueiredo, Eberval Gadelha (Arquivos de Neuro-Psiquiatria, 2023)
Background Subarachnoid hemorrhage (SAH) prognosis remains poor. Vasospasm mechanism might be associated with inflammation. Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been studied as inflammation markers and prognostic predictors.Objective We aimed to investigate NLR and PLR in admission as predictors of angiographic vasospasm and functional outcome at 6 months.Methods This cohort study included consecutive aneurysmal SAH patients admitted to a tertiary center. Complete blood count was recorded at admission before treatment. White blood cell count, neutrophil count, lymphocyte count, platelet count, NLR, and PLR were collected as independent variables. Vasospasm occurrence-modified Rankin scale (mRS), Glasgow outcome scale (GOS), and Hunt-Hess score at admission and at 6 months were recorded as dependent variables. Multivariable logistic regression models were used to adjust for potential confounding and to assess the independent prognostic value of NLR and PLR at admission.Results A total of 74.1% of the patients were female, with mean age of 55.6 ± 12.4 years. At admission, the median Hunt-Hess score was 2 (interquartile range [IQR] 1), and the median mFisher was 3 (IQR 1). Microsurgical clipping was the treatment for 66.2% of the patients. Angiographic vasospasm incidence was 16.5%. At 6 months, the median GOS was 4 (IQR 0.75), and the median mRS was 3 (IQR 1.5). Twenty-one patients (15.1%) died. Neutrophil-to-lymphocyte ratio and PLR levels did not differ between favorable and unfavorable (mRS > 2 or GOS < 4) functional outcomes. No variables were significantly associated with angiographic vasospasm.Conclusion Admission NLR and PLR presented no value for prediction of functional outcome or angiographic vasospasm risk. Further research is needed in this field.
Keywords: Aneurysm; Neutrophils; Lymphocytes; Platelet Count; Subarachnoid Hemorrhage